Inability to perform because of pain/injury in elite adult Irish dance: A prospective investigation of contributing factors - Cahalan, R.; O'Sullivan, Peter; Purtill, H.; Bargary, N.; Ni Bhriain, O.; O'Sullivan, K. (Blackwell Munksgaard, 2015)
© 2015 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd. Previous research in Irish dancing (ID) has recorded high levels of pain/injury. Screening protocols in other genres have been developed to identify at-risk dancers. The aims of the study were to examine the factors that relate to absence from dancing because of musculo-skeletal pain/injury in ID, and to inform guidelines for the development of an evidence-based screening protocol. Baseline subjective data (n=85) and physical data (n=84) were gathered. Subjects completed a monthly online questionnaire for 1 year providing data on general physical and psychological health and rates of pain/injury. Subjects were allocated to a "More Time Absent (MTA)" or "Less Time Absent (LTA)" category depending on their duration of absence from performance over the year. Eighty-four subjects completed the year-long follow-up (MTA: n=32; LTA: n=52). Two hundred seventy-eight complaints of pain/injury were recorded. Factors significantly associated with membership of the MTA group included greater anger-hostility (P=0.003), more subjective health complaints (P=0.026), more severe previous pain/injury (P=0.017), more general everyday pain (P=0.020), more body parts affected by pain/injury (P=0.028), always/often dancing in pain (P=0.028), and insufficient sleep (P=0.043). Several biopsychosocial factors appear to be associated with absence from ID because of pain/injury. Biopsychosocial screening protocols and prevention strategies may best identify at-risk dancers.